O7 Brainstem evoked potentials (BEP) z score is a predictor of disability progression in patients with clinically isolated syndrome. Issue 9 (September 2017) - Pavlovic, Ivan; Crnosija, Luka; Skoric, Magdalena Krbot; Gabelic, Tereza; Adamec, Ivan; Habek, Mario
Abstract : Objectives: To investigate the role of brainstem evoked potentials (BEP) z score as a predictor of disability progression in patients with clinically isolated syndrome (CIS). Methods: Inthirty-two CIS patients (22 females, mean age 32.56 ± 7.68) latencies of the major components of vestibular evoked myogenic potentials (P13, N23, N10 and P13), brainstem auditory evoked potentials (III and V wave), tongue (P1) and median nerve (P14) somatosensory evoked potentials were analyzed and z score for each EP was calculated and combined into BEP z score. EDSS and brain MRI were performed. Disability progression was defined as an increase in EDSS after one-year of follow-up. The following baseline predictors were analyzed: EDSS, brainstem lesions on the brain MRI and BEP score. Results: Median EDSS of the group was 1.5, and 12 (37.5%) patients had brainstem MRI lesions. Mean BEP z score was 0.0272 ± 0.4783. EDSS increase after one year was identified in 9 (28.1%) patients. Patients with the increase in EDSS had significantly higher BEP z score at baseline, p = 0.027. Results of the multivariate regression analysis revealed BEP z score corrected for EDSS at the baseline and the presence of MR brainstem lesions as a significant predictor of disability progression (OR 12.645, 95%CI 1.08–147.71, p = 0.043). Discussion: The presence of MRI brainstem lesions has been identified as one of the major predictive factors for future disability. Conclusion: BEP z score is associated with disability progression one year after CIS. Significance: Brainstem dysfunction is an important predictor of future disability in CIS. This study was partially funded by the Installation Research project HRZZ UIP-11-2013-2622 of the Croatian Science Foundation.